1972
DOI: 10.1139/o72-054
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Metabolism in Mammals. III. Sex Difference in the Bile Acid Composition of Rat Bile

Abstract: Bile was collected from 12 rats, six of each sex, for the first 5 h following the creation of a biliary fistula. The bile acid content of the bile was analyzed by combined thin-layer and gas chromatographic techniques. Total bile acids and the glycine and taurine conjugates were measured. Although bile volumes and total bile acid outputs were similar in rats of both sexes, significant sex differences were found in the amounts of individual bile acids secreted. The female rat secretes considerably more cholic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 0 publications
2
22
1
Order By: Relevance
“…Although Yousef et al [17] demonstrated that secretion rates of cholic acid and lilhocholic acid were greater in females, while (3-muricholate, deoxycholate and hyodeoxycholic acid secretory rates were less than in males, we have found less marked differences in pool constituents in adult rats. The per centage of cholic acid and muricholate in the pools of the two sexes were almost identical, while deoxycholic and chenodeoxycholic acid levels in females were approximately half the male levels.…”
Section: Discussioncontrasting
confidence: 81%
“…Although Yousef et al [17] demonstrated that secretion rates of cholic acid and lilhocholic acid were greater in females, while (3-muricholate, deoxycholate and hyodeoxycholic acid secretory rates were less than in males, we have found less marked differences in pool constituents in adult rats. The per centage of cholic acid and muricholate in the pools of the two sexes were almost identical, while deoxycholic and chenodeoxycholic acid levels in females were approximately half the male levels.…”
Section: Discussioncontrasting
confidence: 81%
“…The diethyl ether extracts were pooled, checked for radioactivity and then evaporated under nitrogen. Previous studies in our laboratory confirmed that these conditions of alkaline hydrolysis were equally effective for both glycine and taurine conju gated bile acids [11]. The completeness of the hydroly sis was indicated by the absence of 1-14C radioactivity in the diethyl ether extracts.…”
Section: Introductionsupporting
confidence: 51%
“…2-5% of the total bile acids were present in 2-3 peaks, which were not identified by our method. The final concen tration of the bile acids was calculated on the basis of reference to the internal standard [11]. Plasma bile acids were determined by the enzyme method [13], Student's t test was used for the statistical analysis, with p > 0.05 indicating no significant difference.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of chenodeoxycholate and lithocholate in serum and bile, as well as the total pool of these potentially hepatotoxic bile acids, is greater in female compared with male rats (39,40). The male rat has greater 60-hydroxylase activity than females and converts chenodeoxycholate and lithocholate to muricholic acid (41).…”
Section: Resultsmentioning
confidence: 99%